The Samsung way : transformational management strategies from the world leader in innovation and design - Song, Chae-yong, 1964- (McGraw-Hill Education, 2014)
Based on ten years of research and interviews with 80 top executives, this is the first definitive guide to the groundbreaking management principles that transformed a lagging electronics company into one of the most successful brands in the world. Combining professional insights from Samsung insiders with practical applications for managers, executives, and CEOs, this book shows you how to: speed up decision making and execution on a bigger scale; create a convergence synergy among diversified businesses, while staying competitive in core businesses; and mix and match Western and Eastern management styles. --